Genomic Epidemiology in Filarial Nematodes: Transforming the Basis for Elimination Program Decisions - Hedtke, Shannon M.; Kuesel, Annette C.; Crawford, Katie E.; Graves, Patricia M.; Boussinesq, Michel; Lau, Colleen L.; Boakye, Daniel A.; Grant, Warwick N. (Frontiers in Genetics, 2020)
Onchocerciasis and lymphatic filariasis are targeted for elimination, primarily using mass drug administration at the country and community levels. Elimination of transmission is the onchocerciasis target and global elimination as a public health problem is the endpoint for lymphatic filariasis. Where program duration, treatment coverage, and compliance are sufficiently high, elimination is achievable for both parasites within defined geographic areas. However, transmission has re-emerged after apparent elimination in some areas, and in others has continued despite years of mass drug treatment. A critical question is whether this re-emergence and/or persistence of transmission is due to persistence of local parasites—i.e., the result of insufficient duration or drug coverage, poor parasite response to the drugs, or inadequate methods of assessment and/or criteria for determining when to stop treatment—or due to re-introduction of parasites via human or vector movement from another endemic area. We review recent genetics-based research exploring these questions in Onchocerca volvulus, the filarial nematode that causes onchocerciasis, and Wuchereria bancrofti, the major pathogen for lymphatic filariasis. We focus in particular on the combination of genomic epidemiology and genome-wide associations to delineate transmission zones and distinguish between local and introduced parasites as the source of resurgence or continuing transmission, and to identify genetic markers associated with parasite response to chemotherapy. Our ultimate goal is to assist elimination efforts by developing easy-to-use tools that incorporate genetic information about transmission and drug response for more effective mass drug distribution, surveillance strategies, and decisions on when to stop interventions to improve sustainability of elimination.